Death conceptions through the times - Giacoia Júnior, Oswaldo (Medicina (Ribeirao Preto), 2005)
The goal of this article is to present some elements that exhibit the historic aspect of the death experience, in a such a way that offers subject for a reflexion about the various meanings the symbolic expression of death assume in funereal rituals, religious cults and artistic manifestations in different cultures.